Implementing DDD for automatic test case generation - Wacharapong Nachiengmai (2020)
© 2020 by the authors. Software testing is a necessary process to ensure quality of software. Unfortunately, it is usually perceived as a very difficult process for inexperienced software developers. Defect-driven Development (DDD) is a novel development concept which aims to bridge such gap. DDD helps inexperienced developers to automatically generate essential test cases and scripts from defect information collected from a knowledge base. This research describes an implementation of the concept as well as its performance evaluation. The result suggests that this technique helps beginners to create an equivalent effectiveness level of unit test compared to experts in both term of time used and defect density.